Developmental Pathways to Borderline Personality Disorder - Chanen, Andrew M.; Kaess, Michael (Current psychiatry reports, 2012)
This paper reviews recent studies of biological and environmental risk and protective factors and patterns of continuity leading to borderline personality disorder (BPD). It focuses on prospective studies of children and adolescents and studies of young people with borderline pathology, reporting findings from genetics, neurobiology, experimental psychopathology, environmental risk, and precursor signs and symptoms. Studies of individuals earlier in the course of BPD demonstrate relatively consistent environmental risk factors, but neurobiological and experimental psychopathology findings are still inconsistent. Also, temperamental and mental state abnormalities that resemble aspects of the BPD phenotype emerge in childhood and adolescence and presage the BPD syndrome in adolescence or adulthood. Further work is required to better understand the roles that all these factors play in the developmental pathways to BPD and to increase their specificity for BPD in order to facilitate prevention and early intervention.